Effect of titanium addition on structure, corrosion resistance and mechanical properties of aluminum coatings on NdFeB by ion-beam-assisted magnetron sputtering. (November 2020) - Lin, Yicheng; Zhu, Qihang; Zheng, Bizhang; Hu, Fangqin; Yang, Lijing; Song, Zhenlun; Xu, Cheng; Li, Zhi-Feng
Abstract: Titanium has been added in the Al coatings on sintered NdFeB magnets by ion-beam-assisted magnetron sputtering to improve the mechanical properties of coatings without corrosion resistance deterioration. The effect of Ti addition on structure, mechanical and electrochemical properties of Al coatings has been investigated, complemented by x-ray diffraction and transmission electron microscopy. The results show that the ion-beam-assisted magnetron co-sputtering of Al and Ti obtains a single-phase polycrystalline structure of Al–Ti solid solution. With the increasing Ti content, the coating structure becomes denser and the grain size is reduced. Both the mechanical and wear properties of the coatings are improved with the addition of Ti where the hardness of the Al–Ti coating increases with the increasing amount of Ti. Polarization and EIS testing results show that the titanium-doped coatings have an enhanced corrosion resistance by comparison with pure Al coatings when Ti content is lower than 4.3 at.%. Highlights: Al–Ti coatings with 0–8.7 at.% Ti are fabricated by ion-beam-assisted magnetron sputtering. A polycrystalline single phase structure of solid solution is obtained. Increasing Ti content leads to significant grain refinement and enhancement of hardness, wear property and corrosion resistance. Al-4.3 at.%Ti coating show a hardness four times than that of Al and a corrosion current one magnitude lower than that of Al.